Application and progress of blood flow restriction training in improving muscle mass and strength in the elderly - Yuan, Junlin; Wu, Li; Xue, Ziao; Xu, Guodong; Wu, Yuxiang (Frontiers in Physiology, 2023)
As an emerging training method, blood flow restriction training has been proved to promote the growth of muscle mass and strength. In recent years, it has been gradually applied in different populations. However, there are few studies on how blood flow restriction training affects muscle mass and strength in the elderly. The relevant literature is compiled and summarized in this study. Through the comparison of blood flow restriction training with traditional training methods and its application in the elderly, it shows that blood flow restriction training can effectively increase muscle mass and strength, prevent muscle atrophy, improve cardiopulmonary function, facilitate injury and postoperative rehabilitation, and intervene in related degenerative diseases as a training method suitable for the elderly,. The main mechanism of blood flow restriction training promoting muscle mass and strength growth is metabolic stress response, including muscle fiber recruitment, protein synthesis signal pathway activation, hormone secretion, etc., and is also related to cell swelling caused by pressure. At present, although the application of blood flow restriction training in the elderly population is increasing, there is a lack of personalized programs. In the future, more research on the dose effect and safety of blood flow restriction training is needed to develop more accurate personalized training programs.